DELVING INTO WRITING STRATEGIES AND DIFFICULTIES OF PRIMARY LANGUAGE LEARNERS - Papadopoulos, Isaak (Educological discourse, 2021)
Writing has been regarded as a most challenging language skill; which has been placed at the center of the research and teaching activity over the last decades. Writing skill along with reading are the two key-skills that shape the context of literacy in a target language while special emphasis is placed on developing and empowering different aspect of students’ literacy repertoire to students even from an early age. This paper presents and describes a multidimensional study which was designed and carried out to investigate primary education students’ difficulties in writing Greek texts. In parallel; the study aimed at investigating the strategies that employed by the students throughout the writing phases. To this end; thirty-five 10-year-old students attending Greek primary education classes took part in this study during the school year of 2020 – 2021. The students lived in Larissa; a city in Central Greece and they participated upon receiving the agreement of their parents. They were engaged in semi structured interviews related to writing a text and they were also invited to complete specifically designed questionnaires focusing on both students’ writing difficulties and the strategies they employ pre- while and post- writing texts in Greek. Both the interviews and the record protocols have been designed and developed by the researcher in an attempt to focus on the students’ writing profile in multidimensional way. Following the data processing; the findings indicated that students were acquainted with their difficulties in writing texts in the Greek language. However; through the study it was released that the students do not make a regular use of writing strategies during their writing activity. Thus; the author of the article presents suggestions for further research and educational practice in primary education contexts.